2021
DOI: 10.1007/s40519-021-01230-4
|View full text |Cite|
|
Sign up to set email alerts
|

Orthorexia nervosa and Instagram: exploring the Russian-speaking conversation around #opтopeкcия

Abstract: This mixed-methods study explored the conversation around orthorexia nervosa (ON) on Instagram from a Russian-speaking perspective. Two quantitative data sources were implemented; a comparative content analysis of posts tagged with #opтopeкcия (n = 234) and #orthorexia (n = 243), and an online questionnaire completed by Russian-speakers (n = 96) sharing ON-related content on Instagram. Additionally, five questionnaire participants were interviewed, four of which identified with having (had) ON. Russian-speaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…A crucial barrier to recovery from ON was its invisibility at both a societal-level and within formal diagnostic criteria. This finding is consistent with other research, in which people with ON have reported a widespread lack of awareness, resulting in confusion and delegitimisation of disordered eating [26,27]. A lack of recognition of ON at a diagnosticand societal-level may ultimately cause it to go undetected and under-reported, thus potentially exacerbating severe medical consequences, psychological distress, and impairments in other important areas of functioning [6,8]; whereas better recognition of ON may lead to improved access to and quality of treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A crucial barrier to recovery from ON was its invisibility at both a societal-level and within formal diagnostic criteria. This finding is consistent with other research, in which people with ON have reported a widespread lack of awareness, resulting in confusion and delegitimisation of disordered eating [26,27]. A lack of recognition of ON at a diagnosticand societal-level may ultimately cause it to go undetected and under-reported, thus potentially exacerbating severe medical consequences, psychological distress, and impairments in other important areas of functioning [6,8]; whereas better recognition of ON may lead to improved access to and quality of treatment.…”
Section: Discussionsupporting
confidence: 93%
“…However, the relationship between social media and ON-as well as other eating disorders-is far more complex, with research showing that different types of engagement with social media, frequency of usage, and reasons for usage are important factors in eating disorder symptomology [21][22][23]. Importantly, social media can also provide valuable recovery spaces for people with ON [24][25][26]. For example, Valente et al [24] reported that while social media can fuel ON behaviours, the spaces afforded by social media can also be valuable stimuli for recovery, providing a counterculture to mainstream sociocultural ideals of health and beauty through the promotion of body positivity and intuitive eating.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial barrier to recovery from ON was its invisibility at both a societal-level and within formal diagnostic criteria. This nding is consistent with other research, in which people with ON have reported a widespread lack of awareness, resulting in confusion and delegitimization of disordered eating [25,26]. A lack of recognition of ON at a diagnostic-and societal-level may ultimately cause it to go undetected and under-reported, thus potentially exacerbating severe medical consequences, psychological distress, and impairments in other important areas of functioning [6]; whereas better recognition of ON may lead to improved access to and quality of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…However, the relationship between social media and ON -as well as other eating disorders -is far more complex, with research showing that different types of engagement with social media, frequency of usage, and reasons for usage are important factors in eating disorder symptomology [20][21][22]. Importantly, social media can also provide valuable recovery spaces for people with ON [23][24][25]. For example, Valente et al [23] reported that while social media can fuel ON behaviours, the spaces afforded by social media can also be valuable stimuli for recovery, providing a counterculture to mainstream sociocultural ideals of health and beauty through the promotion of body positivity and intuitive eating.…”
Section: Introductionmentioning
confidence: 99%